Life After Death in a Chinese Community - BIN RAMLI, MOHD HAFIZOL AMIN; BINTI MAZLAN, NUR AMELIA; BINTI AZMI, SITI AIDA; BIN AWANG BULAT, MUHD SARJI; KAUR, PARVEEN (Trends in Undergraduate Research, 2018)
According to San Fillipo (2006), death is not the end of one’s existence, but rather than a transition from one life to another. However, it is different based on how the society and individuals see the concept of death itself and how they understand about it. Thus, this article aims to explore the understanding of the relationship between culture and religion that become their identity in terms of death and life after. Qualitative approach is adopted for this study. Indeed, interview and empirical observation were used to obtain quality data. Keywords: Buddhism, Chinese, community, culture, life after death, Taoism